Comparing Percutaneous Coronary Intervention and Coronary Artery Bypass Graft in Treatment of Non-ST-segment Elevation Acute Coronary Syndromes: A Systematic Review and Meta-Analysis Study - Amirmohammad Khalifehsoltani; Enwa Felix Oghenemaro; Ahmed Hussein Zwamel; Rekha M.M.; Manish Srivastava; Reza Akhavan-Sigari (European Journal of Translational Myology)
Aims: The objective of this study is to compare the effectiveness and safety of percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) in the treatment of non-ST-segment elevation acute coronary syndromes (NSTE-ACS).